Capillary transit time heterogeneity inhibits cerebral oxygen metabolism in patients with reduced cerebrovascular reserve capacity from steno-occlusive disease. Issue 3 (March 2023) - Vestergaard, Mark B; Iversen, Helle K; Simonsen, Sofie Amalie; Lindberg, Ulrich; Cramer, Stig P; Andersen, Ulrik B; Larsson, Henrik BW
The healthy cerebral perfusion demonstrates a homogenous distribution of capillary transit times. A disruption of this homogeneity may inhibit the extraction of oxygen. A high degree of capillary transit time heterogeneity (CTH) describes that some capillaries have very low blood flows, while others have excessively high blood flows and consequently short transit times. Very short transit times could hinder the oxygen extraction due to insufficient time for diffusion of oxygen into the tissue. CTH could be a consequence of cerebral vessel disease. We examined whether patients with cerebral steno-occlusive vessel disease demonstrate high CTH and if elevation of cerebral blood flow (CBF) by administration of acetazolamide (ACZ) increases the cerebral metabolic rate of oxygen (CMRO2 ), or if some patients demonstrate reduced CMRO2 related to detrimental CTH. Thirty-four patients and thirty-one healthy controls participated. Global CBF and CMRO2 were acquired using phase-contrast MRI. Regional brain maps of CTH were acquired using dynamic contrast-enhanced MRI. Patients with impaired cerebrovascular reserve capacity demonstrated elevated CTH and a significant reduction of CMRO2 after administration of ACZ, which could be related to high CTH. Impaired oxygen extraction from CTH could be a contributing part of the declining brain health observed in patients with cerebral vessel disease.